2020
DOI: 10.5009/gnl19097
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrent Colorectal Polyps

Abstract: The recurrence of colorectal polyps is caused by various factors and leads to the carcinogenesis of colorectal cancer, which ranks third in incidence and fourth in mortality among cancers worldwide. The potential risk factors for colorectal polyp recurrence have been demonstrated in multiple trials. However, an article that pools and summarizes the various results is needed. This review enumerates and analyzes some risk factors in terms of patient characteristics, procedural operations, polyp characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 117 publications
0
30
0
Order By: Relevance
“…Several factors are reportedly associated with polyp recurrence, including age, sex, lifestyle, genetic background, polyp characteristics, and procedural factors [9,[27][28][29][30]. The present study compared the baseline clinical characteristics of both the patients and the colorectal polyps.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several factors are reportedly associated with polyp recurrence, including age, sex, lifestyle, genetic background, polyp characteristics, and procedural factors [9,[27][28][29][30]. The present study compared the baseline clinical characteristics of both the patients and the colorectal polyps.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence rates of different types of polyps widely range from 1 to 43% [6]. Specific factors have been reported to contribute to polyp recurrence, such as age, sex, lifestyle, and polyp characteristics [9]. Obesity and the body mass index (BMI) have long been studied as risk factors for polyp recurrence [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A series of factors have been reported to associate with polyp recurrence, e.g. age, gender, lifestype, genetic background, characteristics of polyps, procedural factors [8,[20][21][22][23]. This study compared the baseline clinical characteristics of patients, as well as of colorectal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Identi cation of risk factors that are predictable for recurrence of colorectal polyps is crucial for protecting at-risk individuals against CRC. Various factors are reported to impact the recurrence rate of polyps, such as gender, age, lifestyle, histology features [8]. Leo et al reported that metabolic factors accelerated colorectal adenoma recurrence [9].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence rates of different types of polyps widely range from 1% to 43% [6]. Speci c factors have been reported to contribute to polyp recurrence, such as age, sex, lifestyle, and polyp characteristics [9]. Obesity and the body mass index (BMI) have long been studied as risk factors for polyp recurrence [10][11][12].…”
Section: Introductionmentioning
confidence: 99%